ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN AKIDAH AKHLAQ: SEBUAH TINJAUAN FILOSOFIS-EPISTEMOLOGIS - Salsabila Arum Az Zahro Putri1; Kiki Cahya Muslimah; Salsabila Ramadhani Fauzia (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to examine the opportunities and challenges of using artificial intelligence in the teaching of Islamic creed and ethics through a philosophical and epistemological approach that explores learning behaviors. This research employs a qualitative design based on a literature review, with data drawn from national and international journals, academic documents, and relevant research reports. Analysis was conducted using content analysis, which includes conceptual categorization, theoretical synthesis, and philosophical interpretation linked to Islamic epistemology and pedagogical practices. The findings indicate that artificial intelligence offers opportunities such as broader access to learning, faster conceptual guidance, and increased engagement in the study of Islamic creed. However, artificial intelligence also presents challenges in the form of algorithmic bias, weakened source verification, and a shift in authority from scholars to digital systems. This study concludes that artificial intelligence can be constructively integrated when educators maintain epistemological and ethical control, thereby ensuring that aqidah education retains its methodological foundation.